Negative Effects of Brand Extension - Jalees, Tariq; Tariq, Nadia (JISR management and social sciences & economics, 2010)
Academicians in general, and students in particular, have recently started idealizing and romanticizing hypotheses-based empirical studies, so much so, that they incorporate hypotheses in their reports and papers, whether there is any need for them or not. Inthis paper, the authors have demonstrated how a non-hypothesis based research must be conducted and structured. The literature review section of this paper starts with broader concepts such as "brands", "brand image" which then have been narrowed to conceptual definitions and arguments related to brand extension, followed by arguments of different authors on negative effects of brand extensions. Subsequently, the constructs derived through literature survey have been summarized and "cited". The developed questionnaire was administered to a sample of 204 respondents, which were empirically analyzed and the results have been compared with the corresponding critical issues related to negative effects of brand extensions derived through literature survey. The results show that if brand extension is not executed properly, it will adversely affect image and sale of core brand as was the case with 7 up, when it extended to "7-up Gold". Similarly, if there is closeness between parent brand and extended brand or if extended brand is more successful, it will hurt core brand as was the case with Miller Light. If there is no associating between core brand and extended brand, then it will hurt extended brand as were the cases of extension of Ponds Tooth Paste and Colgate Kitchen Entrees are cases in point.